Gambaran Kejadian Bullying dan Aspek Mental Siswa Sekolah Dasar Kelas 5 dan 6 - George, Omega K. M.; Kaunang, Theresia M. D.; Dundu, Anita E. (e-CliniC, 2026)
Abstract: Bullying among elementary school students is a frequent issue and has a significant impact on children’s emotional condition, behavior, and mental health. This phenomenon needs to be examined comprehensively to understand its types and implications among fifth- and sixth-grade students. This study employed a mixed-methods approach, specifically an explanatory sequential design. Quantitative samples were obtained through stratified random sampling using the Olweus Bully/Victim Questionnaire-Revised (OBVQ-R), and interviews were conducted with selected victims and perpetrators to explore their mental aspects and subjective experiences. The results obtained 437 students of fifth- and sixth- grade at Malalayang as respondents. Bullying occurred quite frequently, predominantly in the form of verbal bullying, followed by emotional and physical bullying, with students involved as perpetrators, victims, or both. The mental impacts identified included anxiety, fear of attending school, decreased concentration, low self-esteem, and emotional distress, with several cases showing more severe symptoms. In conclusion, bullying among fifth- and sixth-grade students at Malalayang area still occurs and has a significant impact on students’ mental well-being.  Keywords: bullying; mental aspect; elementary school students    Abstrak: Bullying pada siswa sekolah dasar merupakan masalah yang sering terjadi dan berdampak signifikan terhadap kondisi emosional, perilaku, dan kesehatan mental anak. Fenomena ini perlu ditinjau secara komprehensif untuk memahami bentuk kejadian serta implikasinya pada siswa kelas 5 dan 6 di wilayah Malalayang. Penelitian ini menggunakan metode penelitian campuran, khususnya desain sekuensial eksplanatori. Sampel kuantitatif diperoleh melalui stratified random sampling dengan menggunakan kuesioner Olweus Bully/Victim Questionnaire-Revised (OBVQ-R), serta dilakukan wawancara pada korban dan pelaku terpilih untuk menggali aspek mental dan pengalaman subjektif mereka. Hasil penelitian mendapatkan 437 siswa kelas 5 dan 6 di wilayah Malalayang sebagai responden. Bullying cukup banyak terjadi dengan bentuk yang dominan berupa bullying verbal, diikuti emosional dan fisik, dan siswa terlibat sebagai pelaku, korban, maupun pelaku sekaligus korban. Dampak mental yang muncul meliputi kecemasan, ketakutan bersekolah, penurunan konsentrasi, rendah diri, dan distress emosional, dengan beberapa kasus menunjukkan gejala yang lebih berat. Simpulan penelitian ini menunjukkan bahwa bullying pada siswa Sekolah Dasar kelas 5 dan 6 di wilayah Malalayang masih terjadi dan memberikan dampak signifikan terhadap aspek mental siswa. Kata kunci: bullying; aspek mental; siswa sekolah dasar